Paradoxical pacing spikes during a wide complex tachycardia in biventricular defibrillator. What is the mechanism? Is it undersensing due to troubleshooting?. Issue 3 (3rd March 2022) - Leventopoulos, Georgios; Koufou, Eleni‐Evangelia; Koros, Rafail; Perperis, Angelos; Davlouros, Periklis
Abstract : We present the case of a 68‐year‐old man with a cardiac resynchronization therapy‐defibrillator Medtronic device implanted 3 years ago, admitted to our hospital due to a wide complex tachycardia with unexpected pacing spikes inside QRS complexes. Although that could be easily attributed to ventricular undersensing, more complicated mechanisms are involved, including the origin of the tachycardia, the parameters of the device, and the position of the device and the leads.